Imperialism within the Margins - Spurlin, W. author. aut Link
IX, 182 p.
Keywords: Through focusing on the sexual politics that have emerged out of post-apartheid South Africa, Spurlin investigates textual and cultural representations of same-sex desire outside of the Euroamerican axes of queer culture and politics, and considers the ways in which queer cultural productions in southern Africa both intersect with and resist these.